Murine Chronic Pancreatitis Model Induced by Partial Ligation of the Pancreatic Duct Encapsulates the Profile of Macrophage in Human Chronic Pancreatitis - Peng, Cheng; Tu, Guangping; Yu, Li; Wu, Peng; Zhang, Xianlin; Li, Zheng; Li, Zhiqiang; Yu, Xiao (Frontiers in Immunology, 2022)
Immune responses are an integral part of the pathogenesis of pancreatitis. Studies applying the mouse model of pancreatitis induced by partial ligation of the pancreatic duct to explore the pancreatic immune microenvironment are still lacking. The aim of the present study is to explore the macrophage profile and associated regulatory mechanisms in mouse pancreatitis, as well as the correlation with human chronic pancreatitis (CP). In the present study, the mouse model of pancreatitis was induced by partial ligation of the pancreatic duct. Mice in the acute phase were sacrificed at 0, 4, 8, 16, 32, 72 h after ligation, while mice in the chronic phase were sacrificed at 7, 14, 21, 28 days after ligation. We found that the pancreatic pathological score, expression of TNF-α and IL-6 were elevated over time and peaked at 72h in the acute phase, while in the chronic phase, the degree of pancreatic fibrosis peaked at day 21 after ligation. Pancreatic M1 macrophages and pyroptotic macrophages showed a decreasing trend over time, whereas M2 macrophages gradually rose and peaked at day 21. IL-4 is involved in the development of CP and is mainly derived from pancreatic stellate cells (PSCs). The murine pancreatitis model constructed by partial ligation of the pancreatic duct, especially the CP model, can ideally simulate human CP caused by obstructive etiologies in terms of morphological alterations and immune microenvironment characteristics.